Evaluation of a human urine barbiturate test to screen for pentobarbital euthanasia of dogs and cats. (March 2022) - Stern, Adam W.; Muralidhar, Manavi; Cole, Cynthia
Pentobarbital is used commonly to euthanize animals. Occasionally during a death investigation, it is necessary to determine whether a cat or dog was euthanized via pentobarbital overdose. Screening for the detection of barbiturates including pentobarbital can be performed using commercial immunochromatographic tests. We used a commercial immunochromatographic test for barbiturates in humans to screen for barbiturates in urine collected postmortem from 20 dogs and 20 cats to determine whether they had been euthanized with pentobarbital. Additionally, we analyzed the urine for pentobarbital using liquid chromatography–mass spectrometry as a confirmatory test. Screening and confirmation testing revealed 100% agreement between the tests and with the euthanasia status of each animal. Our results support the use of the immunochromatographic test for the screening of urine collected postmortem to assess for the presence of barbiturates, specifically pentobarbital, used for euthanasia.